Aeration performance of weirs - Baylar, A; Bagatur, T (Water Research Commission, 2000)
The concentration of dissolved oxygen (DO) in the waters of rivers and streams is very important to the quality and existence of aquatic life. Hydraulic structures increase the amount of DO in a river system, even though the water is in contact with the structure for only a short period of time. The same quantity of oxygen transfer that normally would occur over several kilometres in a river can occur at a single hydraulic structure. The primary reason for this accelerated oxygen transfer is that air is entrained into the flow in the form of a large number of air bubbles which greatly increase the surface area available for mass transfer. Plunging overfall nappes from weirs are a particular instance of this, and the aeration properties of such structures have been studied widely in the laboratory and field over a number of years. This paper looks at the aeration performance of weirs having different cross-sectional geometry. It is demonstrated that the aeration efficiency of the triangular notch weir generally is better than for the other weirs.